Environmental Impacts of Hydropower: The Role of Dissolved Oxygen Level in Water Ecosystem - KC, Trishna; Paudel, Pratibha; Regmi, Prakash; Khanal, Atit; Basyal, Nishchal (Mid-West University Journal of Engineering & Innovation, 2025)
This paper reports the effects on Environment due to the use of Hydropower. Hydropower is considered to be one of the most used, ecofriendly and sustainable source of energy in Nepal. Besides its various advantages it shows some adverse effects on Environment. One of the high efficient and potential hydropower project named “Padam Khola Hydropower” from Dailekh district is taken as the research area. . Padam Khola Hydropower is selected as the focal region for our research study since the hydropower project requires decent amount of in-flow and also provides decent output (4.8 MW). As the hydropower provides quite satisfactory output, it requires water input in generous amount too, due to which it might carry the potential to disturb aquatic ecosystem. Aquatic ecosystem relies on different ecological and synthetic factors too. Dissolved Oxygen (DO) level is considered one of the key factor for healthy existence of aquatic biodiversity. This research aims to evaluate the DO level of research area. For the study and evaluation of DO level Iodometric titration method is used. Iodometric Titration Method is wide in use due to its accuracy, budget friendly property. The primary objective of this research paper is to evaluate the effect of DO level due to the hydropower. According to Environmental Protection Agency (EPA) DO level less than 5mgL-1 ppm is considered to be in stressful situation for aquatic ecosystem. Moreover, survival of aquatic ecosystem is nearly impossible for the DO level lesser than 3 mgL-1 ppm. Lesser amount of DO level indicates scarcity of oxygen in the water, which can have adverse effects aquatic ecosystem. Meanwhile the results of the research conclude the DO level of research area to be 3.5 mg L-1 which indicates the average existence of aquatic biodiversity.